A new species of Ilex sect. Ilex (Aquifoliaceae) from Guangdong, China - Jiang, Lei; Wu, Lin-Fang; Huang, Guan-Yun; Yu, Jia-Rong; He, Bi-Sheng; Xu, Ke-Wang (Phytotaxa, 2020)
A new species, Ilex jiangmenensis, is described from Gudoushan Provincial Nature Reserve of Jiangmen City, a coastal city in southern Guangdong, China. It was observed to grow in rock crevices or beside the evergreen broad-leaved forests in the mountains of Gudoushan and Nanfengshan at an elevation of 50–550 m. The new species differs from its morphologically most similar species I. pingheensis by its much smaller leave blade, acute or short acuminate apex of leave blade, pistillate inflorescences with fascicles 1–2(–4)-flowered, and staminate inflorescences with individual branches of the fascicles (1)–3-flowered.